Inflammatory myofibroblastic tumor of the ileocecal area complicated by intussusception: a case report in a child - He, Guohou; Luo, Yonghan; Wang, Yanchun; Bai, Qiang (Frontiers in Pediatrics, 2025)
Inflammatory myofibroblastic tumor (IMT) is a rare mesenchymal tumor that can occur in multiple organs. This case report presented an unusual instance of ileocecal IMT in a child complicated by secondary intussusception. A 2-year-6-month-old male was admitted with abdominal pain and fever for 15 days, progressing to currant jelly stools for 2 days. Physical examination revealed a right abdominal mass, and emergency laparotomy confirmed ileocolic intussusception with a firm mass in the ileocecal region. Pathological examination confirmed the diagnosis of IMT. IMT as a secondary cause in pediatric ileocecal intussusception is rare when encountering an atypical intussusception with a suspect lead-point, IMT should be considered.